Cultural heritage and tourism: possibilities of a sustainable relationship - Conti, Alfredo Luis (2015)
Conservation of cultural heritage and tourism are closely related, since historic monuments and sites constitute basic resources to attract visitors. In our capacity of conservators, we have usually worked to preserve the tangible substance of heritage as a means to preserve values. But when the values may differ according to different stakeholders or interested public, among them tourists, we face new challenges related in some case to the proper use of heritage or to the proper interpretation of those values by local communities and visitors. Dedication of cultural heritage to tourism may produce benefits but also some risks if proper planning is not in place; among them the surpassing of the carrying capacity, problems with interpretation of heritage’s values and meanings and the process of gentrification. In this framework, the purpose of this paper is presenting some reflections on the relationship of cultural heritage and tourism and on the role and impact of cultural tourism on heritage conservation.